Infectious Cavernous Sinus Thrombosis Presenting as Temporal Arteritis—A Case Report - Sabir, Rizwan (Neurohospitalist, 2020)
Cavernous sinus thrombosis (CST) is rare and can present with various nonspecific symptoms. The high mortality rate of this disease is largely due to delayed recognition and treatment. We report a case who presented with unrelenting headache and was diagnosed with temporal arteritis (TA) but did not respond to steroids. Imaging helped make the CST diagnosis and the patient responded well to treatment. This case reiterates the importance of early recognition and treatment of CST, and reminds physicians to include CST as an essential differential diagnosis of TA.